Numerical simulation of hyperelastic behaviour in aneurysm models - Ribeiro, J.E. (2019)
The aneurysm is a fragile region on the wall of a blood vessel that causes it to form a bulge. In limiting situations, this weakening can lead to vessel disruption. The main goal of this work was to understand how the deformation of the aneurysm occurs when subjected to an internal pressure similar to blood pressure. The strain state of the aneurysm will allow to define which regions are subject to higher stresses and which can give an indication of potential rupture. To carry out this study we have employed a numerical approach using a commercial software (Ansys®). With this software the pressure caused by the fluid was calculated using known parameters through the experimental measurement of the pressure drop. It was possible to define a velocity profile for the fluid and to characterize its flow through the channel. The aneurysm was subjected to a pressure previously determined for the fluid, simulating the pressure to which the channel is subjected by the bloodstream. Note that the current study have always taken into consideration that the blood vessels have a hyperelastic behaviour, defined through experimental stress/strain curves. Analysing the obtained results, it was verified that the expansion of the aneurysm is predominant in its lateral regions where the greater strain values were obtained. In these regions is where a greater risk of vessel rupture can occur.